Incorporating MicroRNA into Molecular Phenotypes of Circulating Tumor Cells Enhances the Prognostic Accuracy for Patients with Metastatic Breast Cancer. (12th July 2019) - Tan, Weige; Liang, Gehao; Xie, Xinhua; Jiang, Wenguo; Tan, Luyuan; Sanders, Andrew J.; Liu, Zihao; Ling, Yun; Zhong, Wenjing; Tian, Zhenluan; Lin, Wanyi; Gong, Chang
Abstract: Background: The molecular phenotype of circulating tumor cells (CTCs) was associated with clinical outcome of patients with breast cancer. CTCs isolated from patients with metastatic breast cancer (MBC) display a unique microRNA (miRNA) expression profile. The aim of this study was to enhance the prognostic accuracy of the CTC phenotype in patients with MBC, by incorporating miRNA into a combined prediction model. Subjects, Materials, and Methods: CTCs were detected by CellSearch and enriched by magnetic cell sorting. miRNA deep sequencing and quantitative polymerase chain reaction were used to screen and verify potentially CTC‐specific miRNA candidates. Patients with MBC were enrolled from two independent cohorts, and overall survival (OS) and chemotherapy response were analyzed. Results: We screened and identified that miR‐106b was an upregulated molecule in patients with MBC with CTC ≥5/7.5 mL ( n = 16) compared with patients with CTC = 0/7.5 mL ( n = 16) and healthy donors ( n = 8). The expression of CTC‐specific miR‐106b correlated with vimentin and E‐cadherin in CTC and acted as an independent factor for predicting OS (hazard ratio 2.157, 95% confidence interval [CI] 1.098–4.239, p = .026). Although CTC‐specific miR‐106b, E‐cadherin, and vimentin showed a prognostic potential independently, the prognostic performance for OS based on the combination of three markers was significantly enhanced in Cohort 1 (area under the curve [AUC] 0.752, 95% CI 0.658–0.847, n = 128) and further validated in Cohort 2 (AUC 0.726, 95% CI 0.595–0.856, n = 91). Besides, a combined model incorporating miR‐106b was associated with therapy response. Conclusion: The phenotypic assemblies of CTC incorporating miR‐106b show enhanced prognostic accuracy of overall survival in patients with MBC. Implications for Practice: In order to enhance the prognostic accuracy of the circulating tumor cell (CTC) phenotype in patients with metastatic breast cancer (MBC), this study screened and identified a CTC‐specific microRNA (miRNA), miR‐106b, as an upregulated molecule based on the comparison of miRNA profile between CTCs, primary tumors, and healthy blood donors. By incorporating miR‐106b into a combined prediction model, the prognostic accuracy of the CTC phenotype for patients with MBC was greatly improved in both the training and validation cohorts. This work provides clinical evidence supporting the prognostic potential of CTC‐specific miRNA for patients with MBC. These results indicate that developing CTC‐specific miRNAs as new biomarkers will help to further optimize personalized therapy. Abstract : The molecular phenotype of circulating tumor cells is associated with clinical outcome of patients with breast cancer. The aim of this study was to enhance the prognostic accuracy of the circulating tumor cell phenotype in metastatic breast cancer by incorporating miRNA into a combined prediction model.